Public Transport Subsidies And Affordability In Mumbai, India - Cropper, Maureen L. (The World Bank, 2007)
This paper describes the role of public transport and the nature and incidence of transport subsidies in Mumbai, India. Mumbai has an extensive rail and bus network, and public transport is used for over 75 percent of all motorized trips in Greater Mumbai. Both rail and bus fares in Mumbai are subsidized: BEST, which operates public buses in Mumbai, is also an electric utility, and subsidizes bus fares from electricity revenues. We analyze the incidence of these subsidies, and their effect on mode choice, using data from a survey of households in Greater Mumbai. In Mumbai, as in many cities, the middle class is more likely to use public transport for travel than the poor. The poor, however, also use public transit, and their expenditure on public transit constitutes, on average, a larger share of their income than it does for the middle class. It is, therefore, the case that the poor benefit from transit subsidies in Mumbai, as well as the middle and upper-middle classes; however, the poorest 27 percent of the population receives only 19 percent of bus subsidies and 15.5 percent of rail subsidies. Indeed, 26 percent of the lowest income households surveyed do not use rail, while 10 percent do not use bus, implying that they receive no transit subsidies. Expenditure on transport accounts for 16 percent of income in the lowest income category (<5000 Rs./month), with 10 percent of income, on average, spent on bus and rail fares. This percentage, however, is not evenly distributed: it is much higher than 10 percent for households in which workers take the bus or train to work, and lower for households in which the main earner walks to work. Even in these households, however, 12.5 percent of income is spent on transportation. Expenditure on public transport would be even higher if bus fares in Mumbai were not subsidized.